Rezolvati prin metoda substitutiei :
2(x+y)-3y=-11
-4x+3(x+y)=18
Răspunsuri la întrebare
Răspuns de
0
2x+2y-3y=-11
2x-y=-11 |+y
2x=y-11 |+11
y=2x+11
-4x+3x+3y=18
3y-x=18
3•(2x+11)-x=18
6x+33-x=18 |-33
5x= -15 |:5
x= -3.
y=2x+11=2•( -3)+11= -6+11=5.
2x-y=-11 |+y
2x=y-11 |+11
y=2x+11
-4x+3x+3y=18
3y-x=18
3•(2x+11)-x=18
6x+33-x=18 |-33
5x= -15 |:5
x= -3.
y=2x+11=2•( -3)+11= -6+11=5.
Alte întrebări interesante
Limba română,
8 ani în urmă
Istorie,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă